lncRNA NEAT1 Binds to MiR-339-5p to Increase HOXA1 and Alleviate Ischemic Brain Damage in Neonatal Mice - Jing Zhao; Ling He; Lingling Yin (Elsevier, 2020)
Hypoxic-ischemic brain damage (HIBD) is a major cause of fatality and morbidity in neonates. However, current treatment approaches to alleviate HIBD are not effective. Various studies have highlighted the role of microRNAs (miRNAs) in various biological functions in multiple diseases. This study investigated the role of miR-339-5p in HIBD progression. Neonatal HIBD mouse model was induced by ligation of the right common carotid artery. Neuronal cell model exposed to oxygen-glucose deprivation (OGD) was also established. The miR-339-5p expression in mouse brain tissues and neuronal cells was quantified, and the effects of miR-339-5p on neuronal cell activity and apoptosis induced by hypoxia-ischemia were explored. The overexpression or knockdown of long non-coding RNA (lncRNA) nuclear-enriched abundant transcript 1 (NEAT1) in hippocampal neurons was used to determine the effect of lncRNA NEAT1 on the expression of miR-339-5p and homeobox A1 (HOXA1) and apoptosis. Short hairpin RNA targeting lncRNA NEAT1 and miR-339-5p antagomir were used in neonatal HIBD mice to identify their roles in HIBD. Our results revealed that miR-339-5p was downregulated in neonatal HIBD mice and neuronal cells exposed to OGD. Downregulated miR-339-5p promoted neuronal cell viability and suppressed apoptosis during hypoxia-ischemia. Moreover, lncRNA NEAT1 competitively bound to miR-339-5p to increase HOXA1 expression and inhibited neuronal cell apoptosis under hypoxic-ischemic conditions. The key observations of the current study present evidence demonstrating that lncRNA NEAT1 upregulated HOXA1 to alleviate HIBD in mice by binding to miR-339-5p.